Leading Departments with Contingent and Tenure-Eligible Faculty: Strategies and Solutions - Diana L Ashe; Matthew L TenHuisen; Colleen A Reilly (Academic Chairpersons Conference Proceedings, 2017)
Leadership and communication strategies for leading departments that include both contingent and tenure-eligible faculty through three case studies, dealing with 1) voting rights and other claims upon resources; 2) a lack of career milestones, making contingent faculty feel “stuck”; and 3) ways to value contributions of contingent faculty.
Keywords: contingent; adjunct; morale; tenure; communication